2021
DOI: 10.1016/j.bbr.2020.112950
|View full text |Cite
|
Sign up to set email alerts
|

Implicit associative learning relates to basal ganglia gray matter microstructure in young and older adults

Abstract: Older adults are impaired at implicit associative learning (IAL), or the learning of relationships between stimuli in the environment without conscious awareness. These age effects have been attributed to differential engagement of the basal ganglia (e.g. caudate, globus pallidus) and hippocampus throughout learning. However, no studies have examined gray matter diffusion relations with IAL, which can reveal microstructural properties that vary with age and contribute to learning. In this study, young (18-29 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 55 publications
10
18
0
Order By: Relevance
“…Behaviorally, we observed age group differences in IAL as significantly faster reaction times to HF than LF triplets with this difference being larger during late versus early stages of learning and in younger versus older adults (Franco et al, 2020). Of note, no participant was able to accurately identify relationships between the cues and targets, supporting the notion that the associations were learned without awareness and were not the result of different explicit learning strategies between younger and older adults.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Behaviorally, we observed age group differences in IAL as significantly faster reaction times to HF than LF triplets with this difference being larger during late versus early stages of learning and in younger versus older adults (Franco et al, 2020). Of note, no participant was able to accurately identify relationships between the cues and targets, supporting the notion that the associations were learned without awareness and were not the result of different explicit learning strategies between younger and older adults.…”
Section: Discussionsupporting
confidence: 57%
“…Participants completed eight runs of a modified version of the TLT (Howard et al, 2008;Simon et al, 2012), as previously reported (Franco et al, 2020). In this IAL task, participants viewed four open circles presented in a row on a white background.…”
Section: Triplet Learning Taskmentioning
confidence: 99%
See 3 more Smart Citations